Divergent Reactivity of Azides and Diazoalkanes Toward Ferrous Complexes and Isolation of a FeIII Carbene Radical Complex - Zars, Ethan; Pick, Lisa; Kankanamge, Achala; Gau, Michael R.; Carroll, Patrick J.; MacMillan, Samantha N.; Lancaster, Kyle M.; Meyer, Karsten; Mindiola, Daniel J. (Organometallics, 2025)
Treatment of [(tBupyrr2pyr)Fe(OEt2)] (1-OEt2) (tBupyrr2pyr2- = 3,5-tBu2-bis(pyrrolyl)pyridine) with trimethylsilyl azide (N3SiMe3) and subsequent photolysis at 390 nm results in clean formation of [(tBupyrrpyrpyrrNHSiMe3)Fe] (2) as the result of a nitrene being inserted into a tert-butyl C-H bond of the tBupyrr2pyr ligand. Treatment of 1-OEt2 with azidotrimethyltin (N3SnMe3), however, results in isolation of the γ-bound azide adduct ferrous complex, [(tBupyrr2pyr)Fe(N3SnMe3)] (1-N3SnMe3). When treated with diphenyl diazomethane (Ph2CN2), complex 1-OEt2 converts to the iron carbene complex [(tBupyrr2pyr)FeCPh2] (1-CPh2), and the X-ray structure revealed a Fe-CPh2 bond length of 1.964(3) Å. A room temperature magnetic moment of 1-CPh2 indicates an S = 2 spin state, consistent with a high-spin FeIII center antiferromagnetically coupled to a carbene radical anion (CPh2•-). Zero-field 57Fe Mössbauer spectroscopy and Fe K-edge X-ray absorption spectroscopy confirm this assignment. In solution, complex 1-CPh2 rearranges to [tBupyrrpyrC(═CPh2)-C(CMe3)═CH-C(CMe3)═NFe]2 (3) resulting from carbene insertion into the 1-position of the pyrrolide arm of the tBupyrr2pyr ligand and dimerization. Complex 3 possesses two high-spin FeII centers according to 57Fe Mössbauer spectroscopy, with antiferromagnetic coupling between the spin centers. Monitoring the conversion of 1-CPh2 to 3 by UV-vis spectroscopy reveals this process to be first order in 1-CPh2 with a highly ordered transition state evidenced by activation parameters: ΔS‡ = −87.6 ± 25.8 J·mol-1·K-1 and ΔH‡ = 63.1 ± 8.3 kJ·mol-1.
CRIS-Team Scopus Importer:2025-01-31